ENGAGEMENT OF A CHILD WITH CEREBRAL PALSY IN A ADAPTED MOTOR ACTIVITY PROGRAM (Fiep Bulletin - online, 2014)
The objective of this research was to analyze for three consecutive years the time commitment of a child with cerebral palsy in the activities of a program of Adapted Motor Activity. This research, characterized as descriptive case study and qualitative, hade the participation of a child with ataxic cerebral palsy and with 11 years old at baseline. In order to collect data, was selected classes occurred during six semesters (two semesters per year). The prerequisites for the selection of the classes were that the student was present and there was an adult for each disabled child. After selecting classes, it was performed a cursive record allowing to identify the times of classes (total, transition and activities) and times of student engagement (in occupation and waste ). The difference between the total class time was approximately 10 minutes. The times of arrival/departure, transition and activity varied during the six classes analyzed. The class of Semester III showed large intervals of transition (09 minutes 02 seconds) and therefore had less time at activities (33 minutes 58 seconds). This shows the relationship between the transition time with time in activity. In class of Semester III, the child remained in occupation for 88,5% of activity time, while in Semester IV presented more time in waste (44,9%). Throughout the classes analyzed, it became clear evolution of the student, although his time of engagement have not consistently increase linearly. Because it is classes, daily there are changes in the context as regards children and adults, activities planning and classroom organization that act as factors that can influence the engagement time of the child.
Keywords: Adapted motor activity; Engagement time; Cerebral palsy.